Ultrasonic emulsification of Cananga odorata nanoemulsion formulation for enhancement of herbicidal potential - Chamroon Laosinwattana; Naphat Somala; Jantra Dimak; Montinee Teerarak; Nawasit Chotsaeng (Scientific Reports)
Abstract A nanoemulsion was fabricated from Cananga odorata essential oil (EO) and stabilized by incorporation of Tween 80 using ultrasonication. The major constituents of the EO were benzyl benzoate, linalool, and phenylmethyl ester. Differing sonication amplitude (20–60%) and time (2–10 min) were assessed for effects on nanoemulsion droplet size and polydispersity index (PI). The smallest droplet size of 43.98 nm (PI 0.222) was obtained using 40% amplitude for 8 min; this nanoemulsion was evaluated for its droplet characteristics and pre-emergence herbicidal activities on Amaranthus tricolor. FT-IR confirmed ultrasonic emulsification to not affect the EO components. Regarding stability, storage at 4 °C was determined appropriate, with droplet size changing slightly after five weeks. Assays of herbicidal potential showed the coarse emulsion and nanoemulsion to both reduce A. tricolor germination and growth, with the nanoemulsion being more effective at a given concentration and the difference in effectivity correlating to droplet size. Remarkably, treatment with 250 ppm nanoemulsion and coarse emulsion respectively resulted in 100% and 63.75% germination inhibition. Both emulsions decreased seed imbibition and alpha-amylase activity. The highest relative electrolyte leakage was achieved in seed treated with the nanoemulsion. Therefore, this ultrasonic-based nanoemulsion may have utility as bioherbicide alternative.